Analysis of the implementation of new public service community aspirations - Marhaili Sutomo; Desy Misnawati; Isnawijayani; Moh. Hafizni (Jurnal Mantik, 2023)
Development of the development of new autonomous regions requires strong governance support in order to increase the aspirations of the people. Governance that synergizes with government services. This study aims to identify the conditions for the use of the Basic Thought Management System Acceleration (Takepo Axis) at the Secretariat of the Regional People's Representative Council of South Sumatra Province. Analysis using Computer Mediated Communications (CMC) Theory. This qualitative research in collecting data using observation, interviews, and documentation. Data analysis was carried out qualitatively with a purposive sample approach. This research concludes that transparency and speed and accuracy in providing services to the public are the responsibility for performance at the Secretariat of the Regional People's Representative Council of South Sumatra Province. The use of technology in CMC facilitates fast and easy services, and the internet has also inspired the public to monitor the course of public services as an effort to improve service quality